PENGARUH EPS, LDR, DAN ARUS KAS OPERASI TERHADAP HARGA SAHAM EFFECT OF EPS, LDR, AND OPERATING CASH FLOW TO THE STOCK PRICE - George Agust Hermianto, 08.05.52.0127; Hersugondo, Hersugondo (Students Journal of Accounting and Banking, 2013)
The purpose of this study to determine the effect of earnings per share (EPS), loan to deposit ratio (LDR), and operating cash flow on stock prices empirically. This study shows the type of causal research and bersiifat replication of previous research with the study population is a company - a company registered BEI during the 2008 to 2010. Elections were conducted with a purposive sampling method and of the 27 companies acquired 24 companies sampled. The data used are secondary data. This study analyzes the relationship between earnings per share (EPS),), loan to deposit ratio (LDR), and operating cash flow to share price. The statistical method used is multiple linear regression to test the classical assumption first. The results of this study indicate that the partial earnings per share (EPS) have a significant effect on stock prices, the partial loan to deposit ratio (LDR) and a significant negative effect on stock prices, and operating cash flow and no significant negative effect on stock prices as well as variables simultaneously both earnings per share (EPS),), loan to deposit ratio (LDR), and operating cash flows have a significant effect on stock prices in companies listed on the Stock Exchange.Keywords: Earnings Per Share, Loan To Deposit Ratio, Current Kas Operasi